Towards Phenotyping Characteristics and Mechanism of Conduction Delay in Patients With Nonischemic Heart Failure With Reduced Ejection Fraction: Insights From Cardiac Magnetic Resonance Imaging - Zhou, Di; Jiang, Mengdi; Zhu, Leyi; Zhang, Huaying; Wu, Weichun; Xu, Jing; Yang, Wenjing; Wang, Yining; Lian, Xinqiao; Zhou, Wenli; Zheng, Tingting; Sirajuddin, Arlene; et al. (Journal of the American Heart Association, 2025)
Considering that 30% to 40% of patients do not benefit from cardiac resynchronization therapy implantation, it is insufficient to evaluate patients with heart failure with reduced ejection fraction solely based on QRS duration and morphology for guiding cardiac resynchronization therapy decisions and prognosis. A crucial step in addressing this issue is conducting a comprehensive pathophysiological assessment to understand the mechanisms underlying dyssynchrony and inefficient cardiac contraction. This study aims to utilize cardiac magnetic resonance imaging to explore underlying pathophysiological impairments in patients with heart failure with reduced ejection fraction with different QRS morphologies, seeking to identify better indicators for clinical assessment. A retrospective analysis was conducted on 887 consecutive patients with nonischemic heart failure with reduced ejection fraction and prolonged QRS duration who underwent cardiac magnetic resonance imaging, as well as 200 subjects with heart failure with reduced ejection fraction and normal QRS duration as the control group. Patients with left bundle-branch block (LBBB) had a reduced left ventricular/right ventricular ejection fraction ratio compared with controls and patients with right bundle- branch block (RBBB) (LBBB versus RBBB versus controls: 0.6 [0.5, 0.8] versus 0.8 [0.6, 1.1] versus 0.8 [0.6, 1.1]). Late gadolinium enhancement percentage and extracellular volume fraction were significantly larger in patients with RBBB and nonspecific intraventricular conduction delay than in controls and patients with LBBB. Patients with LBBB or intraventricular conduction delay were associated with more impaired left ventricular torsion (LBBB versus intraventricular conduction delay versus RBBB: 0.3°/cm [-0.3, 0.5] versus 0.4°/cm [0.2, 0.7] versus 0.5°/cm [0.2, 0.8]) and strains than those with RBBB. Multivariable logistic regression revealed that the left ventricular/right ventricular ejection fraction ratio and torsion were independent determinants of LBBB. A reduced left ventricular/right ventricular ejection fraction ratio and impaired left ventricular torsion may serve as valuable predictors of dyssynchrony, potentially identifying patients most likely to benefit from cardiac resynchronization therapy.